Detection of Gen Chloramphenicol Acetyl Transferase (CAT ) Salmonella typhi Resistant Chloramphenicol by Polymerase Chain Reaction (PCR) Technique - Supiana Dian Nurtjahyani; Retno Handajani (Biomedical Engineering, 2017)
Objective: Salmonella typhi as a causative agent of typhoid abdominalis many militias, which was resistant to the drug, one of which is chloramphenicol. Detection of Salmonella typhi serologically generally done so if there is a problem in the diagnosis difficult to overcome so it needs a faster diagnosis techniques with accurate results. PCR can be used as an alternative solution to these problems. The purpose of this study was to detect the DNA of Salmonella typhi resistant to chloramphenicol by PCR.Material and methods: The method in this population experimental laboratory conducted in the laboratory biology and laboratory Unirow Tuban ITD Airlangga University Surabaya. Experiment done using PCR from blood samples. Using primer from CAT gene to detect this gene.Result: The results of this study with tank PCR can detect DNA of chloramphenicol resistant Salmonella typhi with a length of 293 bp.Conclusion: The conclusion PCR technique can detect DNA of Salmonella typhi resistant to chloramphenicol.